A Content Analysis of Systematic Review Online Library Guides - Lee, Jennifer; Hayden, K. Alix; Ganshorn, Heather; Pethrick, Helen (Evidence Based Library and Information Practice, 2021)
Objective – Online library guides can serve as resources for students and researchers conducting systematic literature reviews. There is a need to develop learner-centered library guides to build capacity for systematic review skills. The objective of this study was to explore the content of existing systematic review library guides at research universities. Methods – We conducted a content analysis of systematic review library guides from English-speaking universities. We identified 18 institutions for inclusion using a Scopus search to find the institutions with the highest number of systematic review publications. We conducted a content analysis of those institutions’ library guides, coding for the types of resources included, and the stage of the systematic review process to which they referred. A chi-square test was used to determine whether the differences in distribution of the resource types within each systematic review stage were statistically significant. Results – The most common type of resource was informational in content. Only 24% of the content analysed was educational. The most common stage of the systematic review process was conducting searches. The chi-square test revealed significant differences for seven of the nine systematic review stages. Conclusion – We found that many library guides were heavily informational and lacking in instructional and skills focused content. There is a significant opportunity for librarians to turn their systematic review guides into practical learning tools through the development and assessment of online instructional tools to support student and researcher learning.